The Effectiveness of Rehabilitation for Narcotics Users: A Legal Analysis of Law Number 35 of 2009 on Narcotics - Hesty C Simatupang; Muh. Amin Saleh; Muhenri Sihotang; Appe Hutauruk (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
The implementation of rehabilitation for narcotics users in Indonesia continues to demonstrate a gap between the legal framework and law enforcement practices. Although Law Number 35 of 2009 on Narcotics mandates medical and social rehabilitation for narcotics addicts and victims of narcotics abuse, its implementation remains inconsistent due to disparities in legal interpretation, limited access to integrated assessments, unequal rehabilitation facilities, and inadequate post-rehabilitation services. This study aims to analyze the legal regulation governing rehabilitation for narcotics users and to evaluate the effectiveness of its implementation within the Indonesian criminal justice system. The research employs a juridical-empirical approach using statutory, conceptual, and empirical methods. Secondary data were obtained from legislation, court decisions, books, scholarly journals, and official reports issued by the National Narcotics Board (BNN), while primary data were collected through interviews and documentation conducted at the research site. The data were analyzed descriptively using qualitative methods based on the theory of legal effectiveness and the legal system theory. The findings indicate that the existing legal framework provides an adequate basis for rehabilitation; however, its implementation has not yet achieved optimal effectiveness due to structural, instrumental, and cultural barriers among law enforcement institutions. Differences in the interpretation of legal provisions, inconsistent application of integrated assessment recommendations, and unequal availability of rehabilitation services have contributed to legal uncertainty and inconsistent judicial outcomes. Strengthening the legal status of integrated assessment results, establishing consistent prosecution and sentencing guidelines, expanding rehabilitation facilities, improving inter-agency coordination, and implementing evidence-based evaluation of rehabilitation outcomes are necessary to enhance the effectiveness of rehabilitation policies for narcotics users in Indonesia.